Implementación de metodología de las 5S, como programa de mejora continua en ámbito laboral del laboratorio clínico Hospital Isidro Ayora - Minga Calva, Marco Alexander (2023)
The need to implement new techniques and strategies that provide humane care with the highest quality standards is evident in all the services that make up the health system, as is the case of the clinical laboratory area, which, although within the team of health, the personnel of this area is the one that has less contact with the patient, the results published by this entity are crucial to maintain, protect and improve the health status of the population; Through the implementation of the 5S methodology (classify, order, clean, standardize and discipline) and through a previous diagnosis, it will be determined to determine the level of compliance of both the technical and auxiliary service personnel on the correct practice of the aforementioned activities: 94.1% agree that the parameters related to the 5s methodology are almost always met adequately, while 5.9% state that these activities are met occasionally. Through contact with the reality of the laboratory service, it was possible to verify the existence of several weak points of interest for the implementation of the methodology. Thanks to the diagnosis, strategies and tools were designed to reverse and eliminate certain habits, customs and even attitudes that do not allow the clinical laboratory service to improve its efficiency in a notable way. To complement the project, it was necessary to socialize the results obtained through the diagnosis and then train the technical and auxiliary staff of the service in order to generate the empowerment of self-discipline and with it ensure the permanence of the 5S methodology in the work environment. of the HIAL clinical laboratory service